2014
DOI: 10.11646/zootaxa.3838.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the phlebotomine sand fly species (Diptera: Psychodidae: Phlebotominae) of the genera Nyssomyia Barretto, 1962, Bichromomyia Artemiev, 1991, and Migonemyia Galati, 1995, vectors of American cutaneous leishmaniasis in Brazil

Abstract: Phlebotominae, a group of insects with great medical importance especially in Brazil, are responsible for transmitting causal agents of cutaneous and visceral leishmaniasis. In Brazil, the most important species of Leishmania Ross, 1903 are L. (Viannia) braziliensis Vianna, 1911, whose main vectors are Nyssomyia intermedia Lutz & Neiva, 1912, Ny. neivai Pinto, 1926, Ny. whitmani Antunes & Coutinho, 1939 and Migonemyia migonei França, 1920 and L. (Leishmania) amazonensis Lainson & Shaw, 1972, for which Bichrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(29 reference statements)
2
4
0
4
Order By: Relevance
“…The differences in wing shape observed in the present study were similar to those reported by Godoy et al (2014), which are related to the landmarks represented by the apex of vein R1, the fork of veins R2 + R3 + R4, the apex of vein R5 and the apex of vein M4. The wing geometry results obtained by Godoy et al (2014) and in the current study showed the wings of sandflies of the genus Brumptomyia to be larger and shorter than those of species of the other genera. In addition, species of the genera Lutzomyia, Nyssomyia and Micropygomyia were found to have narrow and elongated wings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The differences in wing shape observed in the present study were similar to those reported by Godoy et al (2014), which are related to the landmarks represented by the apex of vein R1, the fork of veins R2 + R3 + R4, the apex of vein R5 and the apex of vein M4. The wing geometry results obtained by Godoy et al (2014) and in the current study showed the wings of sandflies of the genus Brumptomyia to be larger and shorter than those of species of the other genera. In addition, species of the genera Lutzomyia, Nyssomyia and Micropygomyia were found to have narrow and elongated wings.…”
Section: Discussionsupporting
confidence: 90%
“…The wing geometry results obtained by Godoy et al . () and in the current study showed the wings of sandflies of the genus Brumptomyia to be larger and shorter than those of species of the other genera. In addition, species of the genera Lutzomyia , Nyssomyia and Micropygomyia were found to have narrow and elongated wings.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Certainly, two-dimensional imagery is easiest to obtain and manage, such that organisms with relatively flattened body forms will be most tractable (e.g., ticks), although wings of other groups (e.g., mosquitoes and sandflies) may also offer opportunities (Zhou, Ling & Rohlf, 1985; Godoy et al, 2014; Lorenz, Ferraudo & Suesdek, 2015). Small size may present some level of challenge, as we will have to manage the complexities of magnification and associated distortion, but our photo apparatus has been designed to allow addition of accessories to facilitate such challenges in imaging.…”
Section: Discussionmentioning
confidence: 99%